2001
DOI: 10.1089/152581601750288957
|View full text |Cite
|
Sign up to set email alerts
|

Severe Hematopoietic Alterations In Vitro, in Bone Marrow Transplant Recipients Who Develop Graft-Versus-Host Disease

Abstract: Graft-versus-host disease (GVHD) is currently one of the major obstacles for successful allogeneic bone marrow transplantation (BMT). GVHD results from a complex set of interactions between donor T cells and a variety of target tissues from the host. To gain a better understanding of the biology of the human hematopoietic system in GVHD patients, in the present study we have determined the progenitor cell content in bone marrow (BM) samples from BMT recipients, with and without GVHD, and followed their growth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…Of note, progenitor levels were significantly lower in patients with GvHD (7% of normal marrow levels in patients with GvHD vs. 44% of normal marrow levels in patients without GvHD). These findings corresponded with the severely reduced numbers of fibroblastic progenitors and adherent stromal cells observed in long-term marrow culture in patients with GvHD vs. those without (135).…”
Section: Haematopoietic Niche and Acute Gvhdsupporting
confidence: 72%
“…Of note, progenitor levels were significantly lower in patients with GvHD (7% of normal marrow levels in patients with GvHD vs. 44% of normal marrow levels in patients without GvHD). These findings corresponded with the severely reduced numbers of fibroblastic progenitors and adherent stromal cells observed in long-term marrow culture in patients with GvHD vs. those without (135).…”
Section: Haematopoietic Niche and Acute Gvhdsupporting
confidence: 72%
“…Thus, lower KREC levels coincided with the onset period of classic aGVHD, whereas lower TREC levels were associated with a period of increased incidence of cGVHD. It was previously shown that hematopoietic dysfunction can be exacerbated during GVHD [37][38][39], and hematopoietic cells express both class I and class II HLA proteins, which represent potential targets for direct immunocompetent cell responses. Mensen et al [40] reported that T cell bone marrow infiltration during aGVHD may be associated with delayed B cell recovery and function after HSCT, and a toxic bone marrow microenvironment impairing donor-derived hematopoiesis (eg, B cell output) also could result from GVHD-related cytokine release [41].…”
Section: Discussionmentioning
confidence: 99%
“…Irrespective of the clinical occurrence of GvHD, HSCT itself has been shown to result in long‐lasting reductions in bone marrow cellularity, persistent alterations in T‐ and B‐cell development and functionality, and profound declines in the self‐renewal capacities of hematopoietic stem cells (HSC), although these alterations are not necessarily accompanied by a reduction in the peripheral blood cell counts . Furthermore, these pathologies also occur in patients with complete donor chimerism, indicating that engraftment and graft function are regulated by distinct pathways.…”
Section: Introductionmentioning
confidence: 99%